Harnessing the potential of online marketplaces in the Philippines: Insights from the National Information and Communications Technology Household Survey - Connie Bayudan-Dacuycuy; Lawrence B. Dacuycuy (Asian Development Bank Institute (ADBI), 2022)
Using the Philippines' first-ever nationally representative survey designed for characterizing digital commercial and noncommercial engagements, including ICT use, digital economy, and technology-enabled incidents, we investigate the presence of gendered disparities in online marketplaces. Doing this is consistent with the spirit of a gender and development approach that aims for equal and equitable outcomes between men and women. We verify whether the observed participation of women in online marketplaces results in higher online sales. To establish the determinants of participation and incomes in online marketplaces, we use a Heckman estimator in cognizance of the nonrandom choices people make when they enter online marketspaces. The negative selection indicates that those likely to sell have unobserved attributes negatively correlated with online income. Based on our model's income predictions, men outperform women in online sales. Men still hold the advantage, replicating a trend observed in traditional marketplaces. Results also highlight the importance of skills, digital awareness and habits, selling platforms, and ICT infrastructures. The paper also identifies potential initiatives for online marketplaces.
Keywords: D390; D19; 330; online selling; participation; earnings; Philippines